The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/bhk-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness of deaf females

Abstract: SummaryStudy aim: The aim of the study was to examine the differences in physical fitness between deaf female soccer players and their deaf peers who did not practise any sport.Material and methods: The research involved 13 deaf female soccer players and 16 deaf untrained girls. Physical fitness was assessed by a jump test and the Eurofit test. In the jump test, each participant performed an akimbo counter-movement jump (ACMJ), a counter-movement jump (CMJ) and a spike jump (SPJ) on a force plate. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Moreover, normal-hearing athletes were said to have better values in “harmstring/quadriceps ratio” and “maximum voluntary contraction” values. Buśko et al (2020) reported that deaf female football players had better jump performance than normal-hearing healthy individuals. These results confirm that deaf athletes have lower performance in basic motor features compared to normal athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, normal-hearing athletes were said to have better values in “harmstring/quadriceps ratio” and “maximum voluntary contraction” values. Buśko et al (2020) reported that deaf female football players had better jump performance than normal-hearing healthy individuals. These results confirm that deaf athletes have lower performance in basic motor features compared to normal athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Futsal is a sport consisting of a wide variety of repetitive multiplanar moves of high intensity [28] and needs high anaerobic efficiency and excellent operating capabilities [29]. Some studies have shown that children who cannot hear less than their healthy peers, regardless of gender, are physically fit [30]. Nutrition is an essential element in improving an athlete's success.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…The monitoring and early diagnosis of motor skills and cognitive performance in both healthy and sick people [ 1 , 2 ], including deaf athletes plays an important role [ 3 , 4 ]. The complexity of the mechanisms and the large number of parameters that need to be taken into account make artificial intelligence(AI) a great potential solution for speeding up and increasing the accuracy of such analyses.…”
Section: Introductionmentioning
confidence: 99%